Effects of Surface Charge and Functional Groups on the Adsorption and Binding Forms of Cu and Cd on Roots of indica and japonica Rice Cultivars - Liu, Zhao-Dong; Zhou, Qin; Hong, Zhi-Neng; Xu, Ren-Kou (Frontiers in Plant Science, 2017)
This work was designed to understand the mechanisms of adsorption of Cu and Cd on roots of indica and japonica varieties of rice. Six varieties each of indica and japonica rice were grown in hydroponics and the chemical properties of the root surface were analysed, including surface charges and functional groups (-COO- groups) as measured by the streaming potential and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). Binding forms of heavy metals adsorbed on rice roots were identified using sequential extraction methods. In rice roots exposed to Cu and Cd solutions, Cu existed mainly in both exchangeable and complexed forms, whereas Cd existed mainly in the exchangeable form. The amounts of exchangeable Cu and Cd and total adsorbed metal cations on the roots of indica varieties were significantly greater than those on the roots of japonica varieties, and the higher negative charges and the larger number of functional groups on the roots of indica varieties were responsible for their higher adsorption capacity and greater binding strength for Cu and Cd. Surface charge and functional groups on roots play an important role in the adsorption of Cu and Cd on the rice roots.